Inductive Reasoning Ability of Students Using the Palembang Songket Fabric Context in Rotational Learning in Grade IX - Arika Sari; Ratu Ilma Indra Putri (Universitas Sriwijaya, 2022)
Rotation (rotation) is one of the materials in the transformation of geometry. Rotational learning can be the basis for student understanding geometrically because of its dynamic nature. Rotational learning can allow students to relate some geometric concepts such as congruence and equivalence. The study aims to explore the students’ inductive reasoning in rotation problem through the context of songket Palembang pattern in class IX. This research is related to the Indonesian Realistic Mathematics Approach (PMRI) as a learning approach used. The methodology used in this study is Design Research type validation studies consisting of three stages: preliminary design, experimental design, and retrospective analysis. The study was conducted for IX grade students of SMP Negeri 1 Palembang. The learning path (Hypothetical Learning Trajectory) in design research plays an important role as a research design and instrument. The Hypothetical Learning Trajectory was developed together with a series of activities using the contet of songket Palembang pattern such as pucuk rebung pattern, lepus pattern, lintang pattern, etc. Data collected in the form of video recordings and photos during the learning process, student interviews, student work results, discussion results, and field notes at each meeting. The instruments used include documentation in the form of video recordings and photos, interview sheets, student activity sheets, field note sheets, and the Hypothetical Learning Trajectory (HLT). Media used in this study was the students’ worksheet. The result of this study indicated that exploration using the context of songket Palembang patterns can help inductive reasoning ability on students when solving rotation problem. The conclusion of this study is the use of songket Palembang pattern as starting point in mathematics learning in rotation material helps the students to explore their inductive reasoning skill in solving rotation problems.